Yuzu the Pet Vet : Love and Grow - Book 6 Volume 6 - Ito, Mingo; Goniwich, Julie; Yoo, David (Illustrator at Caramel Tree (Firm)); Nihon Koromubia Kabushiki Kaisha (2010- ) (New York : Kodansha Comics, 2021)
"From her base at the Blue Sky City Bow Meow Animal Hospital, Yuzu continues her compassionate adventures on behalf of troubled pets and their owners. Where is the poor pup Alan's owner? Does Hokuto have what it takes to become a police dog? Where did Chii the hamster go? Can Maro the cow convince Ikuko to love the family farm again? As our pets grow, so do we..." -- Page [4] of cover.
Keywords: Puppies -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Human-animal relationships -- Comic books, strips, etc; Preteen girls -- Comic books, strips, etc; Children of sick parents -- Comic books, strips, etc; Families -- Comic books, strips, etc; Uncles -- Comic books, strips, etc; Comic books, strips, etc. -- Translations into English. -- Japan; Graphic novels -- Translations into English. -- Japan; Veterinarians -- Comic books, strips, etc; Veterinary hospitals -- Comic books, strips, etc; Girls -- Fiction; Veterinary hospitals -- Fiction; Veterinarians -- Fiction; Pets -- Fiction; Dogs -- Fiction; Friendship -- Fiction; Uncles -- Fiction; Children of sick parents -- Fiction; Graphic novels; Animal fiction